In vitro Effect of Photoactive Compounds Curcumin and Chlorophyllin Against Single Strains of Salmonella and Campylobacter - Andrea Urrutia; Leticia Orellana; Katherine S. Sierra; Marco Reina; Juan C. Figueroa; Alexandra P. Jackson; Kenneth S. Macklin; R. Jeffrey Buhr; Dianna V. Bourassa (Journal of Food Protection, 2023)
Salmonella and Campylobacter are two of the most common foodborne pathogens associated with poultry meat. Regulatory restrictions and consumer concerns have increased the interest for plant-derived antimicrobials and emerging novel technologies. The objective of this study was to determine the antimicrobial activity of photoactive compounds curcumin (CUR) and chlorophyllin (CH) followed by activating light exposure for the reduction of Salmonella and Campylobacter. Peroxyacetic acid (PAA) was also evaluated as a poultry industry standard antimicrobial processing aid. CUR and CH were evaluated in 96-well plates at concentrations of 100, 500, and 1,000 ppm, along with PAA at 100, 200, and 300 ppm, or distilled water (DW). Each well was inoculated with 105 CFU/mL of Salmonella Typhimurium or Campylobacter jejuni, and plates were exposed to activating light (430 nm) for 0 or 5 min. No detectable reductions were observed for Salmonella or Campylobacter when treated with CUR, CH, or 100 ppm PAA. However, when Salmonella was treated with 200 ppm PAA, counts were reduced from 4.57 to 2.52 log10 CFU/mL. When Salmonella was treated with 300 ppm PAA, counts were reduced to below detectable levels (5 CFU/mL). Campylobacter was reduced from 4.67 to 2.82 log10 CFU/mL when treated with 200 ppm PAA. However, no further reductions were observed when Campylobacter was treated with 300 ppm PAA (2.50 log10 CFU/mL). These results indicate that CUR and CH were not effective as antimicrobials under the evaluated conditions, particularly in comparison to the commonly used antimicrobial, PAA.